Assessments of Temporal Variations in Haplotypes of 'Candidatus Liberibacter solanacearum' and Its Vector, the Potato Psyllid, in Potato Fields and Native Vegetation. Issue 5 (18th July 2018) - Workneh, Fekede; Paetzold, Li; Silva, Adrian; Johnson, Christopher; Rashed, Arash; Badillo-Vargas, Ismael; Gudmestad, Neil C; Rush, Charlie M
Abstract: The potato psyllid, Bactericera cockerelli (Sulc) (Hemiptera: Triozidae), had been known for nearly a century to cause psyllid yellows of solanaceous crops. However, it has only been a decade since the insect was discovered to transmit the bacterium ' Candidatus Liberibacter solanacearum' (Lso), which putatively causes potato zebra chip disease. This project was initiated to quantify temporal incidences of haplotypes of the psyllid (Central, Southwestern, and Western) and Lso (A, B) in potato fields and in native vegetation. Psyllids were collected from native vegetation in Texas (2011–2014), and from potato fields in Texas and New Mexico (2014–2017). Psyllids were tested for Lso and haplotypes of both psyllid and Lso. In Texas, the Central psyllid haplotype was overwhelmingly dominant both in potato fields and in native vegetation regardless of location and time of collection. However, in New Mexico potato fields, although the Southwestern haplotype was overall dominant, the ratios of individual haplotypes varied among years and within a season. The Southwestern psyllid haplotype was greater in incidence than the Central early but declined later in the season in each of the 4 yr, while the Central haplotype was low in incidence early but increased over time. Lso was detected in all three psyllid haplotypes representing the first report in Southwestern psyllid haplotype. In Texas, Lso haplotype A was more frequently detected than B, but in New Mexico the incidence of positive psyllids was not high enough to make definitive conclusions regarding predominant Lso haplotype.